Phone-based intervention for blood pressure control among Ghanaian stroke survivors: A pilot randomized controlled trial. Issue 6 (August 2019) - Sarfo, Fred Stephen; Treiber, Frank; Gebregziabher, Mulugeta; Adamu, Sheila; Nichols, Michelle; Singh, Arti; Obese, Vida; Sarfo-Kantanka, Osei; Sakyi, Asumadu; Adu-Darko, Nyantakyi; Tagge, Raelle; Agyei-Frimpong, Marian; et al.
Background: The potential of mobile-health (mHealth) technology for the management of hypertension among stroke survivors in Africa remains unexplored. We assessed whether an mHealth technology-enabled, nurse-guided intervention initiated among stroke patients within one month of symptom onset is effective in improving their blood pressure (BP) control. Methods: A two-arm pilot cluster randomized controlled trial involving 60 stroke survivors, ≥18 years, with BP ≥140/90 mmHg at screening/enrollment visit at a medical center in Ghana. Participants in the intervention arm (n = 30) received a Blue-toothed BP device and smartphone with an App for monitoring BP measurements and medication intake under nurse guidance for three months after which intervention was withdrawn. Control arm (n = 30) received usual care. Primary outcome measure was proportion with clinic BP < 140/90 mmHg at month 9; secondary outcomes included medication adherence. Findings: Mean ± SD age was 55 ± 13 years, 65% males. Two participants on intervention and three in control group were lost to follow-up. At month 9, proportion on the intervention versus controls with BP < 140/90 mmHg was 14/30 (46.7%) versus 12/30 (40.0%), p = 0.79 by intention-to-treat; systolic BP < 140 mmHg was 22/30 (73.3%) versus 13/30 (43.3%), p = 0.035. Mean ± SD medication possession ratio was 0.95 ± 0.16 on intervention versus 0.98 ± 0.24 in the control arm, p = 0.56. Interpretation: We demonstrate feasibility and signal of improvement in BP control among stroke survivors in a resource-limited setting via an mHealth intervention. Larger scale studies are warranted. Trial registration: NCT02568137. Registered on 13 July 2015 at ClinicalTrials.gov.